2017
DOI: 10.1186/s12885-017-3159-y
|View full text |Cite
|
Sign up to set email alerts
|

Is cancer a pure growth curve or does it follow a kinetics of dynamical structural transformation?

Abstract: BackgroundUnperturbed tumor growth kinetics is one of the more studied cancer topics; however, it is poorly understood. Mathematical modeling is a useful tool to elucidate new mechanisms involved in tumor growth kinetics, which can be relevant to understand cancer genesis and select the most suitable treatment.MethodsThe classical Kolmogorov-Johnson-Mehl-Avrami as well as the modified Kolmogorov-Johnson-Mehl-Avrami models to describe unperturbed fibrosarcoma Sa-37 tumor growth are used and compared with the Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 52 publications
6
72
0
Order By: Relevance
“…Additionally, other electrode array geometries can be used [Pupo et al, ]. For this, it is necessary to know the growth kinetic of this unperturbed F3II tumor in depth, as proposed in González et al []. In addition, parameter β in the MGE for DC‐perturbed tumors should be modified because the angiogenic/anti‐angiogenesis mechanism should be affected by this physical quantity, although this has not been experimentally proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other electrode array geometries can be used [Pupo et al, ]. For this, it is necessary to know the growth kinetic of this unperturbed F3II tumor in depth, as proposed in González et al []. In addition, parameter β in the MGE for DC‐perturbed tumors should be modified because the angiogenic/anti‐angiogenesis mechanism should be affected by this physical quantity, although this has not been experimentally proven.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter α ( α > 0) was the intrinsic growth rate of the tumor related to the initial mitosis rate. The parameter β ( β > 0) was the growth deceleration factor related to endogenous antiangiogenesis processes by an overexpression of different antiangiogenic molecules (i.e., Angiostatin, Thrombospondin‐1 molecules) [González et al, ]. The parameter α * was the modified tumor growth rate due to DC action.…”
Section: Methodsmentioning
confidence: 99%
“…The classical Kolmogorov-Johnson-Mehl-Avrami (KJMA) and modified Kolmogorov-Johnson-Mehl-Avrami (mKJMA) equations are used firstly to fit experimental data of untreated Sa-37 fibrosarcoma tumor that grows in BALB/c/Cenp mice and agree with the Gompertz and Logistics conventional equations [1]. Recently, it has been proposed a new equation to describe data of the unperturbed Ehrlich and Sa-37 fibrosarcoma tumors based on the conventional Gompertz (CG) equation, named Montijano-Bergues-Bory-Gompertz (MBBG) equation (we refer the reader to see equations (8) and (9) in [2]).…”
Section: Introductionmentioning
confidence: 99%
“…Some preclinical studies support the concept of early treatment for cancer because of the exponential tumor growth kinetics presenting as a clinical symptom . Computational modeling of pancreatic cancer therapy showed that early initiation of systemic therapy resulted in a better survival than a delayed therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Some preclinical studies support the concept of early treatment for cancer because of the exponential tumor growth kinetics presenting as a clinical symptom. 19,20 Computational modeling of pancreatic cancer therapy showed that early initiation of systemic therapy resulted in a better survival than a delayed therapy. 21 Delay of treatment initiation may result in the development of drug-resistant micrometastases 22 and increased angiogenesis around the tumor bed in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%